TOURIST DESTINATIONS: DEVELOPMENT AND ADVERTISING STRATEGIES - Семенюк, Олег А.; Семенюк, Лариса Л. (Journal of Strategic Economic Research, 2024)
On the territory of many communities there are objects that have tourist potential, usually not always realized. They are often written about, spoken about by local historians and government officials, but quite often they are underestimated, underdeveloped, abandoned or ineffective in terms of tourist attractiveness. The theory and practice of tourist destination development should answer the question of how to develop these tourist attractions, how to build advertising strategies, etc. The purpose of the article is to analyze the sources of information, direct and hidden advertising that contribute to the development of a tourist destination. Count Shuvalov’s Palace (Talne, Cherkasy region) was chosen as an example of a specific destination. The article uses historical, analytical, comparative methods, techniques of text and content analysis. There are many castles and palaces in Ukraine that do not require special advertising. They have long been popular tourist destinations, parts of sightseeing routes, and a part of the culture and history of their regions or the country as a whole. However, there are also palaces that are not known to the general public, which began their "tourist history" after Ukraine gained independence, became important for the territories in the context of the history of the region, and are considered as possible tourist attractions for the regional economy. Among them is Count Shuvalov’s Palace, located on the outskirts of Talne, Cherkasy region. In accordance with the typification of destinations, we will consider this object a tourist destination of the local level. Despite the rather lengthy restoration, the palace even now meets the generally accepted "indicators of tourism development capacity". Visits to the palace by individual tourists and groups do not stop, even in view of the restoration work. In addition to simple interest in antiquity, this is facilitated by information sources and advertising of various types. Firstly, it is the interesting and accessible information about the palace that is available in the information space. Secondly, it is the "background" information that draws attention to this tourist destination. Thirdly, it is indirect information disseminated in the media or in everyday discourse, usually of a "scandalous" nature, which, from the point of view of PR technologies, is quite effective and memorable. Fourthly, the existence of the palace’s image in the cultural space. It should be noted that local ethnographers, entrepreneurs, and city authorities are making efforts to make the palace a full-fledged cultural heritage site with significant tourist potential, i.e., to acquire all the characteristics of a tourist destination. An important element of the development of a tourist destination, especially in the socio-cultural aspect, should be its organic fit into the Ukrainian cultural context. It is necessary that the palace is perceived not as a legacy of Count Shuvalov, but as an architectural, cultural and historical object built by Ukrainians on Ukrainian soil, as part of the country’s complex heroic history. In achieving this goal, it is important to cooperate with local historians and the media, and to build a proper PR and advertising strategy. A special role should be played by a variety of promotional products, from TV infomercials to souvenirs. Sites such as the Count Shuvalov’s Palace have great potential and tourist appeal, especially for the central and eastern regions of Ukraine. Their preservation and restoration is important for the development of both domestic and foreign tourism.